For y=x^2-6x-11
complete the square
so roots
set y=0
0=x^2-6x-11
group x terms
0=(x^2-6x)-11
take 1/2 of linear coefient (-6) and square it
-6/2=-3, (-3)^2=9
add positive and neative to inside of parenthasees
0=(x^2-6x+9-9)-11
complete square
0=((x-3)^2-9)-11
expand
0=(x-3)^2-9-11
0=(x-3)^2-20
add 20 to both sides
20=(x-3)^2
sqrt both sides
remember positive and negative roots
+/-2√5=x-3
add 3 to both sides
3+/-2√5=x
so
x=3+2√5 and 3-2√5
It means 3 is multiplied by x
Please find attached photograph for your answer. The answer will be option B.
Answer:
i need more info. that part dont help. if you took pic of the sentence they gv you that would be easier to work with.
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
The equation is:
y = 2x + 3
Put x as 2.
y = 2(2) + 3
y = 4 + 3
y = 7
Put x as 3.
y = 2(3) + 3
y = 6 + 3
y = 9
Put x as 4.
y = 2(4) + 3
y = 8 + 3
y = 11
Put x as 5.
y = 2(5) + 3
y = 10 + 3
y = 13